2013
DOI: 10.1242/jcs.123570
|View full text |Cite
|
Sign up to set email alerts
|

Matched miRNA and mRNA signatures from a hESC-based in vitro model of pancreatic differentiation reveal novel regulatory interactions

Abstract: SummaryThe differentiation of human pluripotent stem cells (hPSCs) to insulin-expressing beta islet-like cells is a promising in vitro model system for studying the molecular signaling pathways underlying beta cell differentiation, as well as a potential source of cells for the treatment of type 1 diabetes. MicroRNAs (miRNAs) are a class of small non-coding RNAs that regulate many biological processes, including cellular differentiation. We studied the miRNA and mRNA expression profiles of hPSCs at five stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 54 publications
(67 reference statements)
2
37
0
Order By: Relevance
“…miR-361 has a proximal NANOG binding site indicating that its dysregulation might be due to the observed up-regulation of NANOG in Alkbh1 -/-mouse ESCs. miR-134 is involved in regulation of SOX2 and NANOG, while miR-27b has been implicated in a range of cell types and processes, but seems to have a role in differentiation [38,44,45]. Less is known about miR-615, however, it has been reported to reside in the Hoxc5 intron in mammals, suggesting a possible role in development as the Hox genes control patterning along the anterior-posterior axis in the developing embryo [43,46].…”
Section: Discussionmentioning
confidence: 99%
“…miR-361 has a proximal NANOG binding site indicating that its dysregulation might be due to the observed up-regulation of NANOG in Alkbh1 -/-mouse ESCs. miR-134 is involved in regulation of SOX2 and NANOG, while miR-27b has been implicated in a range of cell types and processes, but seems to have a role in differentiation [38,44,45]. Less is known about miR-615, however, it has been reported to reside in the Hoxc5 intron in mammals, suggesting a possible role in development as the Hox genes control patterning along the anterior-posterior axis in the developing embryo [43,46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dynamic changes in miR-7 levels were found during pancreatic progenitor differentiation in mice (Nieto et al, 2012) and humans (Joglekar et al, 2009a). Similarly, miR-7 levels increase in human embryonic stem cells differentiated into insulin-producing cell in vitro , suggesting a role for the miRNA in the regulation of endocrine cell differentiation during development (Liao et al, 2013; Wei et al, 2013). Kredo-Russo et al (2012) engineered conditional mice with a miR-7 gene targeted into the Rosa26 locus, which upon crossing with Pdx1-Cre mice allows for the overexpression of miR-7 in pancreatic progenitors.…”
Section: Mirnas and The Acquisition Of β-Cell Identitymentioning
confidence: 99%
“…By performing both gain- and loss-of-function experiments in mice, the above authors found that overexpression of miR15a/15b in pancreatic buds decreased Ngn3 levels and reduced the number of α- and β-cells, whereas blocking miR-15 increased Ngn3 levels after partial pancreatotectomy in mice led to higher levels of Nkx2-2 and NeuroD1, two of its downstream targets. Rfx6 , another Ngn3-dependent gene in endocrine cells, is under tight regulation by two glucose-regulated miRNAs, miR-30d and let-7e (Liao et al, 2013). Others have shown that miR-19b represses insulin gene transcription following engagement of its mRNA target NeuroD1 (Zhang et al, 2011).…”
Section: Mirnas and The Acquisition Of β-Cell Identitymentioning
confidence: 99%
“…Later studies have also proven that miR-7 and miR-375 are essential for pancreatic β-cell differentiation and development [22], and in vitro forced expression of miR-7 or miR-375 helps to differentiate hPSCs into IPCs [23,24]. In addition, a number of other miRNAs, including miR-30d , let-7e , miR-21 , miR-9 , and miR-376 , are also implicated in human pancreatic islet differentiation and development [25,26,27]. …”
Section: Mirnas and Pancreatic β-Cellsmentioning
confidence: 99%